Basophil activation test in food allergy: is it ready for real-time?. Issue 5 (9th October 2021) - Keswani, Tarun; Patil, Sarita U.
Abstract : Purpose of review: Utilization of basophil activation in the diagnosis and monitoring of food allergy has gained increasing recognition. An ex-vivo functional assay, basophil activation reflects clinical reactivity, thereby providing clinically relevant insights. Moreover, as a biomarker of reactivity and tolerance, basophil activation testing (BAT) may provide a useful tool for management of food allergies. Despite its utility, significant limitations of BAT have prevented widespread use. Addressing these limitations will increase the future application and adoption of BAT in food allergy. Recent findings: A number of clinical trials in the past few years have demonstrated the use of BAT in the diagnosis and treatment of food allergy. Specifically, BAT has been found to be a biomarker of tolerance. Summary: Basophil activation testing is an effective biomarker for diagnosis and monitoring of food allergy.